Evidence for Resilient Agriculture (ERA): a meta-data based tool for technology-shift decision in Agriculture in Sub-Saharan Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
ERA has been in development for a number of years. ERA has successfully been piloted with various next users during development and recently has been used to inform investment plans and adaptation plans, passing successful piloting (Stage 2). With its public release in October, ERA entered Stage 3.